Two new seco-polycyclic polyprenylated acylphloroglucinol from Hypericum sampsonii. Issue 1 (12th November 2020) - Zhang, Zi-Zhen; Zeng, Yan-Rong; Li, Ya-Nan; Hu, Zhan-Xing; Huang, Lie-Jun; Gu, Wei; Hao, Xiao-Jiang; Yuan, Chun-Mao
Abstract : Two rare seco-polycyclic polyprenylated acylphloroglucinols (1 and 2 ) were isolated from Hypericum sampsonii . Compounds 1 and 2 showed moderate multidrug resistance (MDR) reversal activity to resistant cancer cells, HepG2/ADR and MCF-7/ADR. Abstract : Hypsampsone A (1 ) and hyperhexanone F (2 ), two novel seco-polycyclic polyprenylated acylphloroglucinols, were isolated from Hypericum sampsonii . Hypsampsone A (1 ) features the first spirocyclic system fused with 5/6/5/5 tetracyclic skeleton. Hyperhexanone F (2 ) represents the second novel 1, 2-seco-bicyclo[3.3.1]-PPAP skeleton. Their structures were established by extensive spectroscopic analysis, computer-assisted structure elucidation software, and calculated electronic circular dichroism spectra. A plausible biogenetic pathway of 1 was also proposed. Compounds 1 and 2 showed moderate multidrug resistance reversal activity to adriamycin (ADR) resistant cancer cell lines, HepG2/ADR and MCF-7/ADR, with the fold-reversals ranging from 16 to 38 at noncytotoxic concentration of 10 μM.